2004
DOI: 10.1111/j.1532-849x.2004.04016.x
|View full text |Cite
|
Sign up to set email alerts
|

Shortened Dental Arch: A Review of Current Treatment Concepts

Abstract: It is generally assumed that dentition has ceased to be a predominant selection factor in the process of human evolution. With differentiation and reintegration of the human species, gross differences in the morphology and physiology of the stomatognathic system have become apparent. Variability and adaptation of this system have proven that deviations from what may be considered ideal are not pathologic but may, in fact, prove to be a range of normality in this general pattern of evolution. The treatment of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 24 publications
(23 reference statements)
1
23
0
Order By: Relevance
“…Thus, prosthodontic output (as requested by dentists) of dental laboratories in Sofia indicates that dentists tend to provide fixed dental prostheses to restore incomplete dentitions to a functional level and not necessarily to complete dentitions. These findings are in line with contemporary treatment concepts, based on the assumption that reduced dentitions can offer sufficient oral function [1416]. Moreover, it has been suggested that fixed rather than removable prostheses should be used even in elderly patients [17].…”
Section: Discussionsupporting
confidence: 79%
“…Thus, prosthodontic output (as requested by dentists) of dental laboratories in Sofia indicates that dentists tend to provide fixed dental prostheses to restore incomplete dentitions to a functional level and not necessarily to complete dentitions. These findings are in line with contemporary treatment concepts, based on the assumption that reduced dentitions can offer sufficient oral function [1416]. Moreover, it has been suggested that fixed rather than removable prostheses should be used even in elderly patients [17].…”
Section: Discussionsupporting
confidence: 79%
“…If missing teeth are untreated, dentists do not gain economically. The question of the SDA becomes less one of effectiveness of treatment and more one of finances (23).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the shortened dental arch (SDA) has been developed as a treatment option for partially edentulous individuals. 1,6,12 There is consensus that ten pairs of teeth are required in occlusion (20 teeth distributed from the 2 nd premolar to the 2 nd premolar in both arches). According to Witter et al, 26 a SDA with three to fi ve occlusal units or functional posterior occluding pairs (POPs), with or without free-end removable partial dentures, provides suffi cient occlusal stability for a prolonged period of time.…”
Section: Conclusõesmentioning
confidence: 99%